Red mud-based heavy metal adsorption material as well as preparation method and application thereof

By combining red mud with chitosan, a composite material with strong crosslinkability is formed, and the material regeneration is achieved using ultrasonic-assisted vulcanization precipitation method, the problem of high cost and complex operation when removing heavy metal pollutants in water bodies in the prior art is solved, and efficient and sustainable heavy metal removal and material regeneration are achieved.

CN119701858APending Publication Date: 2025-03-28KUNMING METALLURGY INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510024297.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, complex operation and low treatment efficiency when removing heavy metal pollutants such as lead, zinc and cadmium in water bodies. The structure of traditional modified red mud materials is unstable, which limits its sustainability and recycling.

Method used

Red mud and chitosan are used as the main raw materials, and the red mud particles are uniformly wrapped by hydrothermal method to form a composite material with strong crosslinkability and stable structure, and the material regeneration is achieved through ultrasonic-assisted vulcanization precipitation method.

Benefits of technology

It realizes low-cost, easy to operate and efficient removal of lead, zinc and cadmium ions in water, and significantly improves the regeneration ability and structural stability of the material. It is suitable for the removal of a variety of heavy metals and the sustainable use of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701858A_ABST
    Figure CN119701858A_ABST
Patent Text Reader

Abstract

The invention discloses a red mud-based heavy metal adsorption material and a preparation method and application thereof, the red mud-based heavy metal adsorption material is prepared from the following raw materials in parts by weight through the steps of pretreatment, main reaction and aftertreatment, the raw materials are red mud and chitosan, and the mass ratio of the red mud to the chitosan is (1-3): (2-4). The red mud-based heavy metal adsorption material is suitable for heavy metal pollutant treatment. The method is simple and convenient in preparation, low in cost and excellent in adsorption performance, lead, zinc and cadmium ions in water can be effectively removed, and the composite material is easy to recycle and regenerate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and specifically relates to a red mud-based heavy metal adsorption material and a preparation method and application thereof. Background Art

[0002] With the acceleration of industrialization, heavy metal pollution such as lead (Pb), zinc (Zn) and cadmium (Cd) has become an important issue in global environmental governance. Lead, zinc and cadmium are typical heavy metal pollutants, which are widely present in wastewater from electroplating, metallurgy, chemical industry and other industries. Due to their high toxicity, long-term accumulation and bioaccumulation, they cause serious harm to the water environment and human health. Therefore, removing heavy metals such as lead, zinc and cadmium from water bodies has become an urgent task in the current field of environmental governance. Although existing technologies such as chemical precipitation and ion exchange have made certain progress, these methods usually have problems such as high cost, complex operation and low treatment efficiency, especially when treating high-concentration heavy metal wastewater, the treatment effect is limited.

[0003] Currently, many researchers have begun to explore the use of new red mud materials to remove heavy metal pollution. However, while traditional modification methods improve material performance, they also have problems such as low efficiency, complex processing, and unstable material structure, which limit the sustainability and recyclability of materials in practical applications.

[0004] Patent CN118908519A discloses a method for in-situ catalytic pyrolysis of red mud waste. The method involves impregnating red mud with citric acid and then calcining it at high temperature to obtain an activated red mud catalyst material for heavy metal pollution control. However, the structure of red mud itself is relatively loose, and even after pyrolysis, it is still not conducive to recycling and reuse.

[0005] Patent CN114849659A discloses a method for preparing a chitosan microsphere adsorbent for removing heavy metal cadmium from water and its application. This method uses chitosan as a matrix, forms active sites by loading lanthanum and iron, and adsorbs heavy metal cadmium in water. However, lanthanum salts and iron salts are high-purity chemical reagents with high costs. In addition, the adsorbent preparation process requires the addition of alkali solution drop by drop through an injection pump and freeze-drying, and the production efficiency is low. In contrast, this patent uses industrial solid waste red mud as the main source of iron and is prepared by chitosan composite. The production cost of the adsorbent is greatly reduced, and multiple heavy metals can be removed at the same time.

[0006] Patent CN116283180A discloses a curing agent that can efficiently adsorb heavy metals in contaminated soil. The method prepares soil heavy metal remediation materials with excellent adsorption performance by mixing adsorbents, gelling agents and admixtures in a specific proportion. However, this method relies on a variety of additives, which increases the complexity and cost of material preparation. In contrast, the present invention uses GPTMS to modify red mud and chitosan to directly wrap red mud, using GPTMS to condense and coordinate red mud and the natural biopolymer properties of chitosan, which simplifies the material preparation process and enhances the cross-linking, regeneration and structural stability of the material.

[0007] Patent CN111841485A discloses a regeneration method for a carbonized modified red mud ceramsite adsorbent, wherein the regeneration process includes mixing the adsorbent with calcium oxide and water for calcification reaction, followed by filtration, rinsing, carbonization treatment and drying to achieve regeneration of the adsorbent. In comparison, the ultrasonic assisted sulfidation precipitation method of the present invention does not require high-temperature carbonization and calcification reaction, and regeneration can be completed only through ultrasound and sulfidation reduction, which is simple to operate and more efficient.

[0008] In view of the shortcomings of the above research, it is very necessary to develop a product and method that can solve the above technical problems. Summary of the invention

[0009] The first purpose of the present invention is to provide a red mud-based heavy metal adsorption material; the second purpose is to provide a method for preparing the red mud-based heavy metal adsorption material; and the third purpose is to provide an application of the red mud-based heavy metal adsorption material.

[0010] The first object of the present invention is achieved in that the red mud-based heavy metal adsorption material is prepared by pre-treatment, main reaction and post-treatment steps of the following raw materials in parts by weight, wherein the raw materials are red mud and chitosan, and the mass ratio of red mud to chitosan is (1-3): (2-4).

[0011] The second object of the present invention is achieved by comprising pre-treatment, main reaction and post-treatment steps, specifically comprising: A. Pre-treatment: 1) Adding water to chitosan in a given formula to prepare a chitosan solution a; 2) Dry the formulated red mud, grind and sieve it, then add water, ethanol and γ-methacryloxypropyltrimethoxysilane (GPTMS) in a ratio of 6:3:1, adjust the pH to 4-5 with 1 mol / L acetic acid, and mechanically stir for 20-28 hours to obtain red mud solution b; 3) adding the red mud solution b into the chitosan solution a, and ultrasonically treating the solution at 60° C. until the red mud is evenly dispersed in the chitosan solution to obtain an evenly dispersed composite solution c; B. Main reaction: 1) adjusting the pH of the composite solution c to 12 with a sodium hydroxide solution and stirring the solution to obtain a uniform hybrid solution d; 2) reacting the hybrid solution d at a temperature of 100-120°C for 18-24h to obtain a material precursor e with a completed crystalline structure; C. Post-processing: 1) Drying, grinding and sieving the material precursor e to obtain material f; 2) The material f was heated to 500°C at a heating rate of 10°C / min in an air atmosphere in a muffle furnace and kept warm for 90 minutes. After cooling, it was taken out and washed with water several times until the pH of the material was neutral to obtain a red mud-chitosan composite magnetic adsorption material g.

[0012] 3) The chitosan-red mud composite material g is magnetically screened by a magnet with a magnetic induction intensity of 0.2~1.0 Tesla to obtain a chitosan-red mud composite material with good magnetic properties, namely, the red mud-based heavy metal adsorption material RM / CTS.

[0013] The specific operations are as follows: Step 1) mixing chitosan and water in a ratio of 1:2 to prepare a chitosan solution at 60° C.; Step 2) After the red mud is dried, it is ground and sieved, and water, ethanol and γ-methacryloxypropyltrimethoxysilane (GPTMS) are added in a ratio of 6:3:1, and the pH is adjusted to 4-5 with 1 mol / L acetic acid. The red mud solution b is obtained by mechanical stirring for 20-28 hours.

[0014] Step 3) adding the red mud solution into the chitosan solution, and subjecting the solution to ultrasonic treatment at 40kHz-70kHz for 30 minutes to uniformly disperse the red mud in the chitosan solution, thereby obtaining a uniformly dispersed composite solution.

[0015] Step 4) adding a certain concentration of sodium hydroxide solution (1 mol / L) to the composite solution to adjust the pH to 12, and stirring for 2 hours to ensure that the sodium hydroxide reacts completely with the chitosan and red mud to obtain a uniform hybrid solution.

[0016] Step 5) The obtained hybrid solution is transferred to a hydrothermal synthesis reactor with a stainless steel shell and a polytetrafluoroethylene liner, and heated at a temperature of 110° C. for 18 to 24 hours to obtain a complete crystalline structure.

[0017] Step 6) After the reaction, the material was placed in a drying oven at 60°C until the sample was completely dry and ground to 30-60 mesh.

[0018] Step 7) The material is heated to 500°C at a heating rate of 10°C / min in an air atmosphere through a muffle furnace and kept warm for 90 minutes. After cooling, the material is taken out and washed with water several times until the pH value of the material is neutral to obtain a red mud-chitosan composite magnetic adsorption material.

[0019] Step 8) The obtained chitosan / red mud composite material is further screened by a magnet with a magnetic induction intensity of about 0.2 to 1.0 Tesla to obtain a chitosan / red mud composite material RM / CTS with good magnetic properties.

[0020] As a further improvement, the particle size range of the chitosan / red mud composite material is 2 to 3 microns.

[0021] A further improvement is that the red mud is a solid waste generated during the Bayer process of producing alumina.

[0022] A further improvement is that the mass ratio of the red mud to chitosan is 2:1.

[0023] A further improvement is that the optimal hydrothermal synthesis time is 18 hours.

[0024] Desorption of chitosan / red mud composites Step 1) Prepare sodium sulfide desorption solution: Weigh a certain amount of sodium sulfide and dissolve it in deionized water according to the target concentration (0.2-0.5 mol / L) to prepare a uniform desorption solution. Use a pH meter to measure the pH value of the solution to ensure that the pH value of the solution is 10-12.

[0025] Step 2) Weigh a certain amount of red mud sample that has adsorbed heavy metal ions and place it in a glass beaker; add the prepared sodium sulfide desorption solution to the red mud sample at a solid-liquid ratio of 1:10 (10 g red mud corresponds to 100 mL sodium sulfide solution) to form a mixed solution; and stir the mixture with a magnetic stirrer for 6 hours to ensure that the composite material is in full contact with the desorption solution.

[0026] Step 3) Auxiliary ultrasonic cleaning: Place the beaker in the water tank of the ultrasonic cleaning machine, making sure the water level in the cleaning machine water tank is higher than the liquid level in the beaker; Set the working parameters of the ultrasonic cleaning machine: frequency: 40kHz; power: adjusted to a medium level; temperature: 40~50°C; start the ultrasonic cleaning machine and perform ultrasonic-assisted cleaning for 30 to 60 minutes; During the ultrasonic cleaning process, the contact between the sodium sulfide solution and the red mud is enhanced through the cavitation effect, which effectively accelerates the desorption of heavy metal ions.

[0027] Step 4) Solid-liquid separation and red mud regeneration: After ultrasonic cleaning, the red mud mixture is separated from the solid by a vacuum filtration device; the filtrate is collected and stored to detect the heavy metal concentration in the filtrate after desorption; the separated red mud solid is washed with deionized water for multiple times until the pH value of the filtrate is close to neutral; the washed red mud sample is placed in an 80°C drying oven for 12 hours, and the dried material can be used again.

[0028] Adsorption has become one of the mainstream technologies for removing heavy metal pollution from water due to its low cost, simple operation and high efficiency. In recent years, researchers have gradually turned to the development of new adsorption materials to improve treatment efficiency and material regeneration capacity. Red mud and chitosan, as two natural materials, have gradually become research hotspots for new adsorption materials due to their good adsorption performance and environmental friendliness.

[0029] However, although red mud is rich in mineral components such as iron and aluminum and has a certain ability to adsorb heavy metals, its particles are easily dispersed and its structure is unstable, resulting in a decrease in its adsorption performance in practical applications. Chitosan has a certain adsorption capacity due to its rich functional groups (such as amino and hydroxyl groups), adjustability and biodegradability, but its adsorption is poor due to its instability.

[0030] The adsorption material of the present invention is suitable for the treatment of heavy metal pollutants. The method is simple to prepare, low in cost, excellent in adsorption performance, and can effectively remove lead, zinc and cadmium ions in water, and the composite material is easy to recycle and regenerate.

[0031] The present invention has the following advantages: Structural stability and cross-linking: Chitosan is used to evenly wrap red mud particles through a hydrothermal method to form a composite material with strong cross-linking and stable structure, avoiding the problem of material dispersion or inactivation in the prior art.

[0032] Magnetic enhancement and easy recycling properties: During the preparation process, only red clay components with strong magnetic properties are screened, so that the material can be quickly recovered through an external magnetic field, which simplifies the operation process and reduces the risk of secondary pollution.

[0033] Strong desorption and regeneration capabilities: The rapid desorption of heavy metals and material regeneration are achieved through the synergistic effect of ultrasound and chemical reagents (such as sodium sulfide). This method can significantly extend the service life of the material and reduce costs.

[0034] Wide pH adaptability: This material exhibits excellent adsorption performance in the pH range of 1 to 7, overcoming the defect of existing materials that their performance decreases under strong acidic conditions.

[0035] Compared with existing patents, the present invention has significant advantages in energy conservation and environmental protection, material performance optimization and wide application, and provides an efficient and sustainable solution for heavy metal pollution control. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a schematic diagram of the microscopic morphology of the modified red mud biochar prepared in Example 4 of the present invention; Figure 2 is a schematic diagram of the microscopic morphology of the adsorption material of the present invention; Figure 3 Schematic diagram of the magnetism and recyclability of the adsorption material of the present invention. DETAILED DESCRIPTION

[0037] The specific embodiments of the present invention are further described below in conjunction with the examples and drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.

[0038] The red mud-based heavy metal adsorption material of the present invention is prepared by pre-treatment, main reaction and post-treatment of the following raw materials in parts by weight. The raw materials are red mud and chitosan, and the mass ratio of red mud to chitosan is (1-3): (2-4).

[0039] The mass ratio of the red mud to chitosan is 2:1.

[0040] The method for preparing the red mud-based heavy metal adsorption material of the present invention comprises pre-treatment, main reaction and post-treatment steps, specifically comprising: A. Pre-treatment: 1) Adding water to chitosan in a given formula to prepare a chitosan solution a; 2) Dry the formulated red mud, grind and sieve it, then add water, ethanol and γ-methacryloxypropyltrimethoxysilane (GPTMS) in a ratio of 6:3:1, adjust the pH to 4-5 with 1 mol / L acetic acid, and mechanically stir for 20-28 hours to obtain red mud solution b; 3) adding the red mud solution b into the chitosan solution a, and ultrasonically treating the solution at 60° C. until the red mud is evenly dispersed in the chitosan solution to obtain an evenly dispersed composite solution c; B. Main reaction: 1) adjusting the pH of the composite solution c to 12 with a sodium hydroxide solution and stirring the solution to obtain a uniform hybrid solution d; 2) reacting the hybrid solution d at a temperature of 100-120°C for 18-24h to obtain a material precursor e with a completed crystalline structure; C. Post-processing: 1) Drying, grinding and sieving the material precursor e to obtain material f; 2) The material f was heated to 500°C at a heating rate of 10°C / min in an air atmosphere in a muffle furnace and kept warm for 90 minutes. After cooling, it was taken out and washed with water several times until the pH of the material was neutral to obtain a red mud-chitosan composite magnetic adsorption material g.

[0041] 3) The chitosan-red mud composite material g is magnetically screened by a magnet with a magnetic induction intensity of 0.2~1.0 Tesla to obtain a chitosan-red mud composite material with good magnetic properties, namely, the red mud-based heavy metal adsorption material RM / CTS.

[0042] A. In step 1), the mass ratio of chitosan to water is 1:2.

[0043] A. The grinding and screening in step 2) is grinding through a 140-mesh sieve.

[0044] A. The mass percentage of γ-methacryloxypropyltrimethoxysilane (GPTMS) described in step 2) is 5%.

[0045] The frequency of the ultrasonic treatment in step A3) is 40-70 KHz, and the time of the ultrasonic treatment is 20-40 min.

[0046] B. The concentration of the sodium hydroxide solution shown in step 1) is 0.5-1.5 mol / L; the stirring reaction time is 1.5-2.5 h.

[0047] C. The drying in step 1) is carried out at a temperature of 50-70°C; and the washing is carried out with deionized water to a neutral pH value.

[0048] The application of the red mud-based heavy metal adsorption material of the present invention is the application of the red mud-based heavy metal adsorption material in the preparation of heavy metal adsorption products.

[0049] The present invention is further described below with specific implementation cases: Example 1 Preparation of red mud adsorption material 200 g of air-dried red mud sample was ground using a porcelain mortar and passed through a 140-mesh sieve, and then repeatedly rinsed with deionized water until the pH was neutral.

[0050] Example 2 Preparation of modified red mud adsorption material Red mud modified material: 200 g of air-dried red mud sample was ground in a porcelain mortar and passed through a 140-mesh sieve. After being treated with 0.5 mol / L acetic acid, it was heated and calcined in a muffle furnace for 3 hours at a heating temperature of 500 °C, a heating rate of 5 °C / min, and a constant temperature of 500 °C for 90 min to obtain modified red mud biochar.

[0051] Example 3 Preparation of a chitosan and red mud composite modified adsorption material RM / CTS Red mud chitosan composite material: chitosan and water were mixed in a ratio of 1:2 and prepared into chitosan solution at 60°C; red mud was dried and ground through a 140-mesh sieve, and water, one inch and 5% (mass fraction) GPTMS were added in a ratio of 6:3:1 in sequence and mechanically stirred for 24 hours to obtain red mud solution. The red mud solution was added into the chitosan solution and ultrasonically treated at 40kHz~70kHz for 30 minutes to uniformly disperse the red mud in the chitosan solution to obtain a uniformly dispersed composite solution.

[0052] A certain concentration of sodium hydroxide solution was added to the composite solution to adjust the solution pH to 12, and stirred for 2 hours to ensure that the coupling agent, chitosan and red mud reacted completely to obtain a uniform hybrid solution. The obtained hybrid solution was transferred to a hydrothermal synthesis reactor with a stainless steel shell and a polytetrafluoroethylene liner, and heated at 110°C for 6 to 24 hours to obtain a complete crystalline structure. After the reaction, the material was placed in a drying oven at 60°C until the sample was completely dried. The dried composite material was ground to 30-60 mesh, calcined at 500°C for 90 minutes under air, and then repeatedly washed with deionized water to a neutral pH value to obtain a chitosan / red mud composite material RM / CTS.

[0053] Take 0.5 g of the red mud adsorption material prepared in Examples 1, 2 and 3, respectively, and pour into 500 mL of the Pb-containing 2+ and Cd 2+ In the solution, Pb 2+ 、Zn 2+ 、Cd 2+ The content of heavy metal ions was 50 mg / L, and the initial pH of the solution was controlled at about 5. After that, the solution was fully reacted at 180 rpm for 10 h. The Pb content in the solution after treatment was tested. 2+ 、Zn 2+ and Cd 2+ The removal rate and pH of each modified red mud were calculated, and the adsorption capacity of each modified red mud was calculated. The results are shown in Table 1.

[0054] Table 1 From the test data in Table 1, it can be seen that compared with the original red mud material and the modified red mud material, the chitosan and red mud composite modified adsorption material RM / CTS has a better effect on Pb in sewage. 2+ 、Zn 2+ and Cd 2+ The adsorption amount of ions was significantly improved, and the removal rate exceeded 96%. Its adsorption capacity was 3.18 times that of the original red mud and 2.17 times that of the modified red mud.

[0055] Example 4 Study on the characteristics of red mud modified materials 200g of air-dried red mud sample was ground with a porcelain mortar and passed through a 140-mesh sieve. After being treated with 0.5mol / L acetic acid, it was heated and calcined in a muffle furnace for 3 hours at a heating temperature of 500℃, a heating rate of 5℃ / min, and a constant temperature of 600℃ for 2h to obtain modified red mud biochar. Its microscopic morphology was observed under a scanning electron microscope (model: Tabletop Microscope 3000), as shown in Figure 2. Figure 1 shown.

[0056] Example 5 Study on the properties of chitosan and red mud composite modified materials The microscopic morphology of the red mud chitosan composite material RM / CTS prepared in Example 3 was observed under a scanning electron microscope (model: Tabletop Microscope 3000). Figure 2 shown.

[0057] The SEM images of Examples 4 and 5 were analyzed and found that the red mud modified material had a particle shape approximately round under SEM, with a size of about 3 microns, but the particle surface was rough and had a high degree of dispersion. The chitosan and red mud composite modified material had more surface pores, a more uniform particle shape, a smoother surface, and the RM particles were tightly wrapped by the ribbon-like chitosan, and then agglomerated to form a larger cluster structure. Due to the cluster structure, the material showed hydrophobicity, which was more conducive to recycling.

[0058] Example 6 Take 3.9g of sodium sulfide and dissolve it in 100mL of water to prepare a uniform desorption solution, and then use 1mol / L sodium hydroxide solution to adjust the pH of the desorption solution to 8. Take 5g of red mud sample with heavy metal ions and place it in a glass beaker; add the prepared sodium sulfide desorption solution to the adsorbent material sample to form a mixed solution; fully magnetically stir for 6h to allow the composite material to fully contact with the desorption solution. Then put the beaker into the water tank of the ultrasonic cleaning machine. The working parameters of the ultrasonic cleaning machine are: frequency: 40kHz; temperature: 40~50°C; start the ultrasonic cleaning machine and perform ultrasonic-assisted cleaning for 30 minutes. After the ultrasonic cleaning is completed, the red mud mixture is separated from the solid by a vacuum filtration device; the washed adsorbent material sample is placed in an 80°C drying oven and dried for 12 hours. After the dried material, take 0.5g and add 500mL of the Pb-containing to be treated. 2+ 、Zn 2+ and Cd 2 + In the solution, Pb 2+ 、Zn 2+and Cd 2+ The content of heavy metal ions was 50 mg / L, and the initial pH of the solution was controlled at about 5. After that, the solution was fully reacted at 180 rpm for 10 h. The Pb content in the solution after treatment was tested. 2+ 、Zn 2+ and Cd 2+ The removal rate was calculated and the adsorption capacity of each modified red mud was calculated. The above steps were repeated 3 times. The results are shown in Table 2.

[0059] Table 2

[0060] From the test data in Table 2, it can be seen that after three desorption-adsorption cycles, the adsorption of Pb 2+ 、Zn 2+ and Cd 2+ The removal rate and adsorption capacity showed a downward trend, but it was confirmed that the adsorbent material had sustained adsorption performance and could be used multiple times in the treatment of wastewater containing heavy metal ions of lead, zinc and cadmium.

[0061] Example 7 Weigh 5 g of the adsorbent material RM / CTS of Example 3 and 5 g of the adsorbent material of Example 2, respectively, and pour them into an ampoule, followed by adding 20 mL of water. After the addition, shake the ampoule vigorously, and then carefully observe and compare the magnetic strength and recyclability of the two adsorbent materials. The experimental results are shown in the attached figure. Figure 3 shown.

[0062] Depend on Figure 3 It can be seen that the material has good cross-linking and magnetism, and has excellent recyclability compared with other modified red mud.

[0063] Example 8 Take 0.5g of the adsorption material RM / CTS of Example 3 and measure the heavy metal content in the material by inductively coupled plasma mass spectrometry (ICP-MS), including: lead, cadmium, arsenic, copper, zinc, and mercury. Take 5g of the material powder sample, put it in a clean beaker, and add deionized water at a ratio of 1:5. After stirring evenly, let the mixture stand for a period of time (such as 30 minutes to 1 hour), and measure the pH of the solution with a pH meter.

[0064] By comparing the Soil Environmental Quality Agricultural Land Soil Pollution Risk Control Standard (GB15618-2018), the environmental friendliness of this material when used in soil in the future is observed. The results are shown in Appendix 3.

[0065] Table 3

[0066] As can be seen from Table 3, the pH of the adsorption material is 6.5~7.5, and various heavy metal indicators are significantly lower than the screening values ​​of the Soil Environmental Quality Agricultural Land Soil Pollution Risk Control Standard (GB15618-2018). It also has certain application potential in the direction of soil heavy metal remediation in the future.

Claims

1. A red mud-based heavy metal adsorption material, named RM / CTS, characterized in that: The red mud-based heavy metal adsorption material is prepared by pre-treatment, main reaction and post-treatment steps of the following raw materials in parts by weight. The raw materials are red mud and chitosan, and the mass ratio of red mud (RM) to chitosan is (1-3): (2-4).

2. The red mud-based heavy metal adsorption material according to claim 1, characterized in that: The mass ratio of the red mud to chitosan is 2:

1.

3. A method for preparing the red mud-based heavy metal adsorption material according to claim 1 or 2, characterized in that: It includes pre-treatment, main reaction and post-treatment steps, specifically including: A. Pre-treatment: 1) Adding water to chitosan in a given formula to prepare a chitosan solution a; 2) Dry the formulated red mud, grind and sieve it, then add water, ethanol and γ-methacryloxypropyltrimethoxysilane (GPTMS) in a ratio of 6:3:1, adjust the pH to 4-5 with 1 mol / L acetic acid, and mechanically stir for 20-28 hours to obtain red mud solution b; 3) adding the red mud solution b to the chitosan solution a, and ultrasonically treating at 60° C. until the red mud is evenly dispersed in the chitosan solution to obtain a uniformly dispersed composite solution c; B. Main reaction: 1) adjusting the pH of the composite solution c to 12 with a sodium hydroxide solution and stirring the solution to obtain a uniform hybrid solution d; 2) reacting the hybrid solution d at a temperature of 100-120°C for 18-24h to obtain a material precursor e with a completed crystalline structure; C. Post-processing: 1) Drying, grinding and sieving the material precursor e to obtain material f; 2) The material f was heated to 500°C at a heating rate of 10°C / min in an air atmosphere in a muffle furnace and kept at this temperature for 90 minutes. After cooling down, the material was taken out and washed with water for several times until the pH value of the material was neutral, thereby obtaining a red mud-chitosan composite magnetic adsorption material g; 3) The chitosan-red mud composite material g is magnetically screened by a magnet with a magnetic induction intensity of 0.2 to 1.0 Tesla to obtain a chitosan-red mud composite material with good magnetic properties, namely, a red mud-based heavy metal adsorption material RM / CTS.

4. The preparation method according to claim 3, characterized in that: A. In step 1), the mass ratio of chitosan to water is 1:

2.

5. The preparation method according to claim 3, characterized in that: The grinding and screening in step A2) is grinding through a 140-mesh sieve.

6. The preparation method according to claim 3, characterized in that: A. The mass percentage of γ-methacryloxypropyltrimethoxysilane (GPTMS) described in step 2) is 5%.

7. The preparation method according to claim 3, characterized in that: The frequency of the ultrasonic treatment in step A3) is 40-70 KHz, and the time of the ultrasonic treatment is 20-40 min.

8. The preparation method according to claim 3, characterized in that: B. The concentration of the sodium hydroxide solution in step 1) is 0.5-1.5 mol / L; the stirring reaction time is 1.5-2.5 h.

9. The preparation method according to claim 3, characterized in that: C. The drying in step 1) is carried out at a temperature of 50-70°C; and the washing is carried out with deionized water to a neutral pH value.

10. Use of the red mud-based heavy metal adsorption material according to claim 1 or 2 in the preparation of heavy metal adsorption products.